The Effects of Mindfulness-Based Intervention on Shooting Performance and Cognitive Functions in Archers - Wu, Tsung-Yi; Nien, Jui-Ti; Kuan, Garry; Wu, Chih-Han; Chang, Yi-Chieh; Chen, Hsueh-Chih; Chang, Yu-Kai (Frontiers in Psychology, 2021)
This study investigated the effects of a mindfulness-based intervention (MBI) called mindfulness-based peak performance (MBPP) on athletic performance and cognitive functions in archers, as well as the role of psychological status and the dose-response relationship of MBPP in archery performance. Twenty-three archers completed a simulated archery competition and the Stroop task prior to and after MBPP training, which consisted of eight sessions over four weeks, while the mindfulness and rumination levels of the archers were assessed at three time points, namely, before, at the mid-point of, and after the MBPP program. The results revealed that the MBPP program significantly improved the shooting performance (p = 0.002, d = 0.27), multiple cognitive functions (ps < 0.001, d = 0.51 0.71), and mindfulness levels of the archers on the post-test, compared to the pre-test (p = 0.032, ηp2 = 0.15 for general; p = 0.004, ηp2 = 0.22 for athletic). Additionally, negative ruminations level was decreased from the pre-test to the middle-test and post-test (ps < 0.001, ηp2 = 0.43). These findings provide preliminary evidence to support the view that MBPP could serve as a promising form of training for fine motor sport performance, cognitive functions, and specific psychological status, such that it warrants further study.